Look and Leep: How are we doing? An audit of GSH colposcopy clinic from 1 January 2017 to 31 December 2021 - Gaskell, Marlene (Department of Obstetrics and Gynaecology, 2025)
Background: Cervical cancer persists as the second most common cancer in women in developing countries. The prevalence of cervical cancer has markedly decreased in well developed nations, primarily attributed to the implementation of efficacious screening services. Such screening services pose formidable challenges in developing countries. Therefore, the ‘See-and-Treat' strategy has been adopted in South Africa and other developing countries to reduce loss to follow up and prevent patients to present with advanced disease, thereby reducing the morbidity and mortality associated with cervical cancer. The main limitation of this approach is the risk of overtreatment, identified as final histopathology without preinvasive cervical lesion. The objective of our study is to identify the rate of overtreatment at a colposcopy clinic in a tertiary center with extensive experience in colposcopy and to detect possible factors associated with this rate. Methods: This was a retrospective, descriptive cohort study that analyzed data from 715 women who had undergone the ‘See-and-Treat' treatment approach from 2017 to 2021 at Groote Schuur Hospital Colposcopy clinic. Overtreatment was defined as final histopathology results of Cervical Intraepithelial Neoplasia grade 1 (CIN 1) or less. Results: Of the 715 women, there 109 (15.24%, 95% CI 0.13 – 0.18) with a histopathology result of CIN 1 or less. There was a statistically significant association between age and the odds of overtreatment as well as between HIV negative women, when compared to HIV positive women on treatment, and the odds of overtreatment. No statistically significant association was found between smoking status, HIV viral load, CD4 count or parity. Conclusion: The overtreatment rate in this study can be considered acceptable and comparable with rates reported in the literature. HIV negative women should be considered for a biopsy prior to LEEP to decrease risk of overtreatment, but the risk should be weighed against the risk of loss to follow up. Keywords: Cervical intraepithelial neoplasia, Colposcopy, See-and-Treat, Overtreatment, Negative histology.